A Case of Acute Hepatitis E Complicated by Acute Pancreatitis in Eastern India - P, Rudrajit; D, Shubhabrata; P, Sourav; SC, Partha; M, Jayati; R, Bhattacharya (IIUM Medical Journal Malaysia, 2013)
Viral hepatitis may be occasionally associated with acute pancreatitis. Usually the patient presents with abdominal pain in the second or third week of illness. Hepatitis A or E viruses are mostly implicated. HEV related acute pancreatitis was first reported only 12 years ago. We report a case of a young male presenting with acute Hepatitis E infection complicated by pancreatitis. He had an uneventful recovery. This is probably the first report of this association from Eastern India.